Disposition to learning and democratic coexistence in public schools of Peru - Barrientos Mollo, Roberto (2018)
This research seeks to identify the relationship between the disposition to learn and democratic coexistence in students  of schools that implement "Comunidades de Aprendizaje".  It also investigates whether there are significant differences for these same variables in independent samples that consider demographic factors. It is a quantitative research, with  non-experimental, correlational descriptive design.   A total of 9 944 students answered this censal survey, participating all students, from third grade of primary to fifth grade of high school engaged in literary circles in any of the 43 schools of the project located in Lima, Callao, Piura, Cusco, Apurímac, Huancavelica and Puno, both in urban and rural areas. The applied instrument was specifically designed for this research and serves as a baseline for the schools that implement the project. The descriptive results show high and very high levels for the disposition to learn and democratic coexistence.  These two variables show considerable and highly significant (0.01) positive correlation (0.678) and when analyzing them in independent samples, statistically significant differences were found concluding that the highest results are found in female students, at the primary level and in rural areas.